2008
DOI: 10.1115/1.2908431
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling Instabilities in Microchannels and Means for Mitigation by Reentrant Cavities

Abstract: The ability of reentrant cavities to suppress flow boiling oscillations and instabilities in microchannels was experimentally studied. Suppression mechanisms were proposed and discussed with respect to various instability modes previously identified in microchannels. It was found that structured surfaces formed inside channel walls can assist mitigating the rapid bubble growth instability, which dominates many systems utilizing flow boiling in microchannels. This, in turn, delayed the parallel channel instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(60 citation statements)
references
References 17 publications
1
59
0
Order By: Relevance
“…These instabilities occur at lower mass fluxes as the inertia of the incoming liquid is insufficient to prevent the liquid from rushing back. The reasons for instabilities and methods for preventing them have been discussed in a number of publications, including Serizawa et al (2002), , Hetsroni et al (2005), Kandlikar et al (2006), and Kuo and Peles (2008). As a result of the instabilities, the walls of the microchannels remain exposed to the expanding vapor bubble, creating local dry patches on the wall and causing the heat transfer deterioration.…”
Section: Factors Responsible For Heat Transfer Degradation In Microchmentioning
confidence: 99%
“…These instabilities occur at lower mass fluxes as the inertia of the incoming liquid is insufficient to prevent the liquid from rushing back. The reasons for instabilities and methods for preventing them have been discussed in a number of publications, including Serizawa et al (2002), , Hetsroni et al (2005), Kandlikar et al (2006), and Kuo and Peles (2008). As a result of the instabilities, the walls of the microchannels remain exposed to the expanding vapor bubble, creating local dry patches on the wall and causing the heat transfer deterioration.…”
Section: Factors Responsible For Heat Transfer Degradation In Microchmentioning
confidence: 99%
“…Typically with smooth surface microchannels, flow instability can cause temperature and pressure drop fluctuations due to the change of flow pattern and local surface dry-out [43,44]. To study the effect of surface structures on flow instabilities, we In comparison, the structured surface (S4) maintained the liquid film due to the wicking capability of the microstructures (0.002 s<t<0.010 s), until vapor/dry islands formed first at the center instead of the sides of the channel from t=0.012 s (Figure 7).…”
Section: Temperature and Pressure Drop Fluctuationsmentioning
confidence: 99%
“…Furthermore, once the ONB occurs in microchannels, a bubble can grow rapidly and most of the channel cross-section may be occupied by bubbles (Kandlikar and Balasubramanian, 2004;Hetsroni et al, 2005a;Barber et al, 2010). This phenomenon may cause the onset of flow instability leading to a decreased CHF value and significant oscillations of system pressure and heat transfer rate (Hetsroni et al, 2005a;Bergles and Kandlikar, 2005;Kuo and Peles, 2008). Absence of apparent partial boiling prior to fullydeveloped nucleate boiling (Peng and Wang, 1993) and a considerable wall temperature drop at ONB (Piasecka et al, 2004;Qi et al, 2007) were also reported.…”
Section: Introductionmentioning
confidence: 97%
“…Lee et al (2011) also reported that the nucleation incipient conditions at single artificial cavities in their square and rectangular microchannels were well matched with the classical theory presented in section 2 of this article. Kuo and Peles (2008;2009a) reported that the incipient boiling heat fluxes measured for the heated surfaces with artificial reentrant cavities were generally lower than those for a plane surface. This observation would also be the evidence that the ONB condition in microchannels is particularly sensitive to the surface condition.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation